Top executives' school-tie connections and management forecast disclosure - Jianqiao Yu; Ting Luo (China Journal of Accounting Studies (CJAS), 2020)
This paper investigates whether top executives' dependence on social connections has an impact on the information environment of listed companies. Specifically, this paper explores the role of school ties between firms' and suppliers' top executives on management earnings forecasts, an important channel of public information disclosure. We find a negative relation between a firm's school ties with its suppliers and the likelihood/frequency to issue management forecasts, indicating that top executives' school ties in a way substitute management forecasts and become the information channel along the supply chain. Further, we find the association is stronger when the firm faces higher proprietary cost or operational uncertainty, but the association becomes weaker when suppliers have bargaining advantage over the firm. Finally, we find the decrease in management forecast disclosure driven by school-tie connections weakens the access of firm-specific information for external information users, which may put individual investors in a more vulnerable position.
Keywords: 650; School ties; management forecasts; information environment; supply chain